Language-independent talker-specificity in bilingual speech intelligibility: Individual traits persist across first-language and second-language speech. Issue 1 (9th October 2018) - Bradlow, Ann R.; Blasingame, Michael; Lee, Kyounghee
Abstract : The present study provides evidence of a positive correlation between L1 and L2 intelligibility for bilingual talkers. Each talker in a group of Mandarin-English and Korean-English bilinguals was recorded producing simple sentences in each of their languages. The recordings were then presented to native listeners of the language-being-spoken in a test of sentence-in-noise recognition to yield a pair of L1 and L2 intelligibility scores for each talker based on the proportion of words correctly recognized. For all talkers, their L2 speech (i.e., Mandarin- or Korean-accented English) was consistently lower in intelligibility than their L1 speech (i.e., native accented Mandarin or Korean). This dissociation between L1-L2 speech intelligibility was evident in different intelligibility scores at comparable signal-to-noise ratios (as much as 35 percentage points for the Mandarin-English bilinguals) and in the required boost in signal-to-noise ratio to achieve comparable intelligibility (>8–10 dB). Critically, L1 and L2 intelligibility scores within the bilingual talkers were strongly positively correlated: Talkers with relatively high intelligibility in L1 also achieved relatively high intelligibility in L2. These results indicate a persistent influence of talker-specific trait characteristics that combine with, rather than are overwhelmed by, language-specific and dominance-dependent influences in bilingual speech production.